Social Enterprises and the Poor: Enhancing Social Entrepreneurship and Stakeholder Theory - Marie Lisa Dacanay (Copenhagen Business School (CBS), 2012)
This thesis develops a framework for understanding how social enterprises engage the poor and address poverty, a pressing global problem of the 21st century. Using casebased theory building, it studies a theoretical sample of three pairs of Philippine-based social enterprises, where the poor were suppliers, workers, and customers. In half of the cases, the poor were also owners. The research studies the roles and role changes of the poor in these social enterprises, how and why these roles changed, or did not change, and the impact of the roles and role changes, if any, on the social enterprises and the poor. Data for the research was gathered mainly from key informant interviews, published and unpublished organizational documents as well as previous studies done by external consultants on the case subjects. Based on a cross case analysis of the data from the theoretical sample, the thesis develops three models of stakeholder engagement among social enterprises with the poor as primary stakeholders or SEPPS, namely: control, collaboration and empowerment. This thesis provides insights and develops propositions about the importance of stakeholder engagement and the power and limitations of these three models in bringing about social inclusion and poverty reduction. These propositions are suggested to be applicable in countries in the South other than the Philippines where systemic poverty and inequality are exacerbated by the failure of state and market institutions to address the needs of the poor. This thesis makes a contribution to social entrepreneurship and stakeholder theory. It does so by sharing a perspective from the South and giving a voice to the poor as stakeholders. The researcher notes that overall, the poor and the South are under-represented in these discourses. On the whole, social entrepreneurship theorizing has been characterized as embryonic as a topic of academic inquiry. Stakeholder engagement is considered an under-theorized area in stakeholder theory. In developing a framework for understanding stakeholder engagement models involving the poor, this thesis makes a first step towards applying and extending stakeholder theory in SEPPS. The thesis likewise enriches social entrepreneurship theory by conceiving of SEPPS as a global social enterprise model that catalyzes South-North cooperation to address poverty and inequality.
hdl:10398/8513
Keywords: 650